2011
DOI: 10.1108/01443571111104755
|View full text |Cite
|
Sign up to set email alerts
|

The role of actor associations in understanding the implementation of Lean thinking in healthcare

Abstract: Purpose -The importance of networks in effecting the outcomes of change processes is wellestablished in the literature. Whilst extant literature focuses predominantly on the structural properties of networks, our purpose is to explore the dynamics of network emergence that give rise to the outcomes of process improvement interventions. Through the use of ActorNetwork Theory (ANT) we explore the dynamics in the implementation of a process improvement methodology in the complex organisational setting of a UK Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(123 citation statements)
references
References 47 publications
4
106
1
9
Order By: Relevance
“…Having been focused mainly on mass production industries such as automotive and textiles so far, recent studies also explore lean cooperation aspects in service industries such as healthcare (Papadopoulos et al, 2011) and high technology industries such as aerospace (Beelaerts van Blokland et al, 2012). Lean cooperation in the aerospace industry also attracted our attention and will be further explored in this paper.…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…Having been focused mainly on mass production industries such as automotive and textiles so far, recent studies also explore lean cooperation aspects in service industries such as healthcare (Papadopoulos et al, 2011) and high technology industries such as aerospace (Beelaerts van Blokland et al, 2012). Lean cooperation in the aerospace industry also attracted our attention and will be further explored in this paper.…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…Esta metodología se considera aplicable a los procesos relacionados con la salud (Kollberg et al, 2007;Brandao, 2009;Papadopoulos et al, 2011., La Ganga, 2011Mazzocato et al, 2012), así como con los departamentos de emergencia (Piggott et al, 2011;Mazzocato et al, 2012;Martínez et al, 2014;Martínez et al, 2015) debido a que mediante esta los procesos son llevados a cabo con calidad, y cumpliendo con la satisfacción del consumidor (Weinstock, 2008;Morales, 2010;Mannon, 2014 En países desarrollados (Adra, 2005;Aherne, 2007;Bliss, 2009;Brandao, 2009;Sobek y Lang., 2010;Burgess y Radnor, 2013;Breuer, 2013), así como en aquellos considerados como emergentes, se ha comenzado a aplicar lean en servicios de salud (Varkey y Kollengode, 2011;Ponanake et al, 2014;Pestana et al, 2014), pero en países como Colombia estas metodologías son recientes, presentando su aplicación principalmente en empresas de manufactura (Dinas et al, 2009;Arrieta et al, 2010).…”
Section: Introductionunclassified
“…When implementing LP strategies the organization's stakeholders, including employees and managers, interpret and color a management concept like LP based on their interests and motives (Sahlin and Wedlin 2008;Skålén 2002). The interpretation of LP is defined as a process of negotiation between different stakeholders' interests and influences that determine if and how the concept of LP is applied in the specific health care organization (Joosten et al 2009;Papadopoulos et al 2011). Previous research has shown that hospital management's rationale for applying different LP methods and tools within health care mainly includes increased efficiency and worker performance (Mazzocato et al 2010;Poksinska 2010).…”
Section: Sustainable Participation In Odmentioning
confidence: 99%